PENGUATAN NILAI KEAGAMAAN PADA ANAK YANG KURANG DUKUNGAN ORANG TUA MELALUI KEGIATAN MENGAJI BERSAMA DI DESA JENTERA KECAMATAN WAMPU - Aulia Putri, Dwi Kartika; Ade Chita Putri Harahap; Dea Winanda Tambak; Sumiyati Br Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Spiritual development in children is crucial for building their character and faith. However, not all children receive adequate parental support in learning and applying religious principles, particularly in reading the Quran. This inadequate support may be due to parents' busy schedules, lack of knowledge, or lack of attention to their children's religious education. Children who lack guidance will struggle to understand and implement Islamic teachings. This study aims to foster religious values in children who receive little parental attention. The method chosen was a qualitative case study approach, and data were collected through in-depth interviews, observation, and documentation. The findings indicate that Quranic study activities in Jentera Village have brought positive changes, particularly for a child named AZ. They demonstrated improvements in Quranic reading, consistency in worship, and Islamic behavior. Children who previously could not read have now begun to memorize short chapters and pray regularly. Quranic study activities have proven successful in strengthening religious values and building a religious atmosphere through community involvement.